نمذجة السلوك المرن- اللدن لسبائك حديد الصب المستخدمة في تبطين بلاطات مطاحن المواد الأولية في معمل اسمنت طرطوس - شاش, ميساء; سلامة, أحمد; شعبان, حسام (Latakia University Journal -Engineering Sciences Series, 2019)
الهدف من الدراسة معرفة السلوك الميكانيكي لسبائك حديد الصب المختلفة و المستخدمة في تبطين مطاحن الاسمنت. عن طريق إعداد نموذج رياضي لدراسة السلوك المرن- اللدن لهذه السبائك , وبشكل خاص المستخدم منها في معمل اسمنت طرطوس. الدراسة تضمنت تحضير عينات من البلاطات (12×10 cm) و بثخانة (4 cm). تم قياس قساوة العينات, ومن ثم اختبارها على الصدم, باستخدام جهاز خاص, تم تصميمه في سياق البحث والذي يحاكي آلية الصدم التي تتعرض لها البلاطات في المطحنة, ومن ثم قياس قساوتها ثانية لمعرفة أثر الصدم عليها. نظرا لصعوبة إجراء اختبار الشد والضغط على العينات المدروسة, وبالتالي صعوبة التنبؤ بتغير خواصها الميكانيكية بفعل التقسية الانفعالية. تم إعداد نموذج رياضي لدراسة السلوك الميكانيكي, معتمدين في اختيار البارامترات الأساسية للنموذج بالاعتماد على قيم القساوة. أظهرت النتائج العملية أن هذا المعدن يتقسى بفعل الصدم , وما ينتج عنه من تغير حد الخضوع ومتانة المعدن, كما أعطى النموذج نتائج قريبة من النتائج العملية. The objective of this study is to know the mechanical behavior of various alloys of cast iron used in the lining of cement mills, through the preparation of mathematical model to study the elasto-plastic behavior of these alloys, in particular, the alloys used by Tartous cement plant. The study is checks samples of dimensions (12×10 cm) and thickness (4 cm) in order to measure hardness, and impact test using special device which is developed in this research, and it simulates the impact mechanism experienced by the plates in the mill. Finally, the hardness has been measured again to see the effect of impact on these samples. Because of difficulty of carrying out the tensile test on the studied samples, and the difficulty to predict the change of its mechanical properties due to strain hardening. Mathematical model was developed to study the mechanical behavior, relying on the selection of the basic parameters of the model depending on the hardness values. The practical results show that the process of strain hardening resulting from impact leads to change in the hardness and the durability of metal. The model also gave close results to the practical results.